A requirement of dendritic cell‐derived interleukin‐27 for the tumor infiltration of regulatory T cells. Issue 5 (17th January 2014) - Xia, Siyuan; Wei, Jun; Wang, Jingya; Sun, Huayan; Zheng, Wenting; Li, Yangguang; Sun, Yanbo; Zhao, Huiyuan; Zhang, Song; Wen, Ti; Zhou, Xinglong; Gao, Jian‐Xin; et al.
Abstract : IL‐27 promotes immunosuppressive Treg recruitment into tumors, by inducing dendritic cell derived CCL22 production. Abstract : Tregs (Foxp3 + CD4 + ) are enriched in tumors to foster a tolerant microenvironment that inhibits antitumor immune response. IL‐27 is reported to regulate the development and function of Tregs in vitro and in vivo; however, the effects of endogenous IL‐27 on Tregs in the tumor microenvironment remain elusive. We demonstrated that in the absence of DC‐derived IL‐27, Tregs were decreased significantly in transplanted B16 melanoma, transplanted EL‐4 lymphoma, and MCA‐induced fibrosarcoma by using IL‐27p28 conditional KO mice. Further studies revealed that IL‐27 promoted the expression of CCL22, which is established to mediate the recruitment of peripheral Tregs into tumors. Tumor‐associated DCs were identified as the major source of CCL22 in tumor sites, and IL‐27 could induce CCL22 expression in an IL‐27R‐dependent manner. Intratumoral reconstitution of rmCCL22 or rmIL‐27, but not rmIL‐27p28, significantly restored the tumor infiltration of Tregs in IL‐27p28 KO mice. Correlated with a decreased number of Tregs, tumor‐infiltrating CD4 T cells were found to produce much more IFN‐γ in IL‐27p28 KO mice, which highlighted the physiological importance of Tregs in suppressing an antitumor immune response. Overall, our results identified a novel mechanism of action of IL‐27 on Tregs in the context of cancers.